Influence of deep-sea hydrostatic pressure on the tribocorrosion behavior and mechanism of La2O3–TiB2–Ni coating - Zhengyi Li; botai Su; Pengwei Ren; Lei Wen; Dongbai Sun (Journal of Materials Research and Technology)
To understand the tribocorrosion mechanism of TiB2–Ni coating doped with La2O3 in the deep ocean, the wear and corrosion test of La2O3–TiB2–Ni under various hydrostatic pressures was conducted and discussed in 3.5 wt % NaCl solution. The results indicate that the tribocorrosion mechanism of the La2O3–TiB2–Ni coating transitions from abrasive wear with corrosion under 0.1 MPa to abrasive wear with corrosion and adhesive wear under high hydrostatic pressure. The La2O3–TiB2–Ni coating shows significant enhancements in wear resistance and anti-friction properties compared to the TiB2–Ni coating. As the hydrostatic pressure increases from 0.1 MPa to 30 MPa, the self-corrosion current density experiences an approximate increase of 43.6 μA/cm2.